2018
DOI: 10.1016/j.cmet.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Basal Mitophagy Occurs Independently of PINK1 in Mouse Tissues of High Metabolic Demand

Abstract: SummaryDysregulated mitophagy has been linked to Parkinson's disease (PD) due to the role of PTEN-induced kinase 1 (PINK1) in mediating depolarization-induced mitophagy in vitro. Elegant mouse reporters have revealed the pervasive nature of basal mitophagy in vivo, yet the role of PINK1 and tissue metabolic context remains unknown. Using mito-QC, we investigated the contribution of PINK1 to mitophagy in metabolically active tissues. We observed a high degree of mitophagy in neural cells, including PD-relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
464
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(497 citation statements)
references
References 51 publications
32
464
1
Order By: Relevance
“…We wondered whether, by analogy with the role of USP30 in Parkin-overexpressing cells, this increase in mitophagy was dependent on PINK1. Depleting PINK1 did not affect basal levels of mitophagy, in agreement with two recent reports in mitophagy reporter flies and mice [19,20]. However, PINK1 depletion did suppress the enhancement of mitophagy seen upon USP30 knockdown ( Fig 1D).…”
Section: Enhancement Of Basal Mitophagy By Usp30 Depletion Is Dependesupporting
confidence: 92%
“…We wondered whether, by analogy with the role of USP30 in Parkin-overexpressing cells, this increase in mitophagy was dependent on PINK1. Depleting PINK1 did not affect basal levels of mitophagy, in agreement with two recent reports in mitophagy reporter flies and mice [19,20]. However, PINK1 depletion did suppress the enhancement of mitophagy seen upon USP30 knockdown ( Fig 1D).…”
Section: Enhancement Of Basal Mitophagy By Usp30 Depletion Is Dependesupporting
confidence: 92%
“…Accordingly, a number of outer mitochondrial membrane (OMM) proteins, including mitofusins, VDACs and subunits of the translocase of the OMM (TOM) interact with or are ubiquitinated by Parkin during the process of mitochondrial clearance in response to mitochondrial depolarization 23 , suggesting that no specific substrate is required for ubiquitin signalling of mitophagy. However, the finding that loss of PINK1 did not influence basal mitophagy despite disrupting depolarization-induced Parkin activation 24 , suggests that Parkin could participate in maintain mitochondrial integrity by different pathways. Parkin was shown to constitutively associate with the ER and the mitochondrial membranes under basal conditions 2531 implying a potential role for this protein in mitophagy-independent functions, such as the modulation of the proteasome activity, of the mitochondrial–ER interactions and calcium crosstalk and the degradation or targeting of specific mitochondrial and/or mitochondria-related proteins.…”
Section: Introductionmentioning
confidence: 95%
“…Of the various mitochondrial ubiquitin ligases (Covill‐Cooke et al , ), we studied March5 and MUL1, because they are known to be expressed in the nervous system, but it is possible that other ubiquitin ligases are involved. In support of this interpretation, it was recently demonstrated that in transgenic mice expressing a mitophagy reporter, the ablation of PINK1 did not affect the rate of basal mitophagy in neurons (McWilliams et al , ), further indicating that the loss of PINK1‐Parkin in the nervous system can be complemented by other MQC mechanisms.…”
Section: Discussionmentioning
confidence: 86%